2016
DOI: 10.1007/s00270-016-1543-7
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Artery Embolization for Retained Products of Conception with Marked Vascularity: A Safe and Efficient First-Line Treatment

Abstract: RPOC with MV can present with large uterine AV shunt, particularly in case of late management. Uterine artery embolization is an effective and safe first-line treatment, and should be evaluated for this indication in larger prospective trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…Bazeries et al 10 showed that in cases of RPOC with marked vascularity, minimally invasive UAE was an effective and safe first-line treatment. UAE is an effective treatment for post-partum hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bazeries et al 10 showed that in cases of RPOC with marked vascularity, minimally invasive UAE was an effective and safe first-line treatment. UAE is an effective treatment for post-partum hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Hysteroscopic removal of RPOC appears to be an increasingly popular technique associated with long‐term complications and reproductive outcome compared with dilation and curettage . In cases of active bleeding caused by RPOC and under surgical treatment, uterine artery embolization (UAE) is helpful for decreasing hemorrhage . However, while UAE is used to treat post‐partum hemorrhage and fibroids, the effect of UAE on fertility remains controversial and the effect after UAE for RPOC is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously reported, the evacuation procedure for RPOC with marked vascularity in the uterus might cause massive bleeding . Some obstetricians and gynecologists would prefer UAE . Thus, before this protocol involving the maximum laminaria procedure and targeted removal of RPOC, as a cautionary measure, we set up UAE as backup.…”
Section: Discussionmentioning
confidence: 99%
“…Retained products of conception (RPOC) with marked vascularity can cause massive postabortal or post‐partum hemorrhage . These clinical presentations resemble placental polyps and uterine artery pseudoaneurysms .…”
Section: Introductionmentioning
confidence: 99%